2015
DOI: 10.1155/2015/748390
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus Status, Inorganic Phosphorus Forms, and Other Physicochemical Properties of Acid Soils of Farta District, Northwestern Highlands of Ethiopia

Abstract: Soil acidity and low availability of P limit crop production in the highlands of Ethiopia. The objective of this study was to determine the P status, distribution and forms of inorganic P and relate them to selected chemical properties of eight representative acidic surface soil samples from Farta District. Soil pH (H 2 O) varied between 4.74 and 5.50. The moderate to high CEC suggests that besides kaolinite, the soils also contain expandable 2 : 1 clay minerals. Though the total P content was high, the availa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 29 publications
5
29
0
Order By: Relevance
“…This observation corroborates findings by Melese et al . [ 76 ] and Adhami et al ., [ 77 ] but contradicted those reported for less weathered soils. However, the contrary observation of Ca-P following application of ERP treatments in this study could be due to the undissolved rock phosphate.…”
Section: Resultsmentioning
confidence: 99%
“…This observation corroborates findings by Melese et al . [ 76 ] and Adhami et al ., [ 77 ] but contradicted those reported for less weathered soils. However, the contrary observation of Ca-P following application of ERP treatments in this study could be due to the undissolved rock phosphate.…”
Section: Resultsmentioning
confidence: 99%
“…This deficiency of available P on the study area could be due to the high CaCO3 content of the soil since the available P can precipitate in the form of calcium phosphate in calcareous soil. Similarly, Melese et al (2015) reported that in calcareous soil, the available P was low due to the precipitation of P in the form of calcium phosphate.…”
Section: Available Phosphorusmentioning
confidence: 92%
“…Most of the studies reported depletion of cation exchange capacity (CEC), organic carbon (OC), and total nitrogen (TN) (Ashenafi et al, 2010;Yitbarek et al, 2016). Available soil phosphorus (P) was found to be deficient in most soils of cultivated lands (Mekonnen, 2015;Melese et al, 2015). More recently, variations of soil properties such as TN, organic matter (OM), and CEC with topographic positions and soil depth in some areas of north and south Wollo of the Amhara region have been reported (Nahusenay et al, 2014;Alem et al, 2015).…”
Section: Introductionmentioning
confidence: 99%